Global History with Chinese Characteristics Autocratic States along the Silk Road in the Decline of the Spanish and Qing Empires 1680-1796 - Perez-Garcia, Manuel (Palgrave Studies in Comparative Global History, 2021)
This open access book examines perceptions and dialogues between China and Europe by analysing strategic geopolitical sites which fostered commerce, consumption and socioeconomic networks between China and Europe through a particular case study: Macau, connecting with South China, and Marseille in Mediterranean Europe from 1680 to 1800. How did foreign merchant networks and trans‐national communities of Macau and Marseille operate during the eighteenth century and contribute to somehow transfer respectively European and Chinese socio‐cultural habits and forms in local population? What was the degree and channels of consumption of European goods in China and Chinese goods in Europe? Through these questions the book explores the bilateral Sino‐European trade relations and considers how the trans‐national dimension of exotic commodities changed tastes by creating a new type of global consumerism.